Mark-to-market and its effects on community banking during the financial crisis: An examination of perceived risks. Issue 1 (9th February 2015) - Patron, Hilde; Smith, William J.
Abstract : Purpose: – The purpose of this paper is to study the impact of the relaxation of mark-to-market (MTM) standards on community banks' share prices. Mark-to-market valuation of securities became increasingly common in the late 1990s and 2000s, as regulators sought to create more transparent and more current depictions of bank financial positions. However, MTM accounting may be sub-optimal in the presence of severe market frictions, such as those experienced during the financial crisis of the late 2000s. To comply with capital requirements associated with MTM accounting, banks of the late 2000s dramatically liquidated portfolios with potentially solvent assets in illiquid markets, taking huge losses. During the financial crisis, mortgage-backed securities held by banks began to plummet in value. Banks were forced to either liquidate these assets even though there were no buyers or dramatically reduce the values of their portfolios based on fire-sale prices. On a cash-flow basis, these securities had value, as many mortgages bundled in these securities continued to be paid on time; however, with markets frozen, market prices did not reflect this value. Design/methodology/approach: – This study shows that, for a sample of 134 community banks, share prices increased after the MTM relaxation, even after accounting for a variety of other economic factors. Findings: – This paper shows that, perhaps counterintuitively, the steps taken by the Financial Accounting Standards Board to relax MTM accounting standards may have acted as a stabilizing factor on the market price of community bank shares by allowing banks to selectively liquidate assets, boosting asset prices until uncertainty was resolved. Originality/value: – This paper examines the impact of recent changes in accounting standards on the perceived risks associated with the banking sector. It specifically focuses attention on the impacts these changes had on community-based banks within the USA.